Mechanisms of Ischemic Stroke in Patients with Cancer: A Prospective Study. Issue 1 (3rd June 2021) - Navi, Babak B.; Sherman, Carla P.; Genova, Richard; Mathias, Ryna; Lansdale, Kelsey N.; LeMoss, Natalie M.; Wolfe, Julia; Skakodub, Anna; Kamel, Hooman; Tagawa, Scott T.; Saxena, Ashish; Ocean, Allyson J.; et al.
Abstract : Objective: The objective of this study was to examine the pathophysiology of ischemic stroke with cancer. Methods: We conducted a prospective cross‐sectional study from 2016 to 2020 at 2 hospitals. We enrolled 3 groups of 50 adult participants each. The main group included patients with active solid tumor cancer and acute ischemic stroke. The control groups included patients with acute ischemic stroke only or active cancer only. The patients with stroke‐only and patients with cancer‐only were matched to the patients with cancer‐plus‐stroke by age, sex, and cancer type, if applicable. The outcomes were prespecified hematological biomarkers and transcranial Doppler microemboli detection. Hematological biomarkers included markers of coagulation (D‐dimer and thrombin‐antithrombin), platelet function (P‐selectin), and endothelial integrity (thrombomodulin, soluble intercellular adhesion molecule‐1 [sICAM‐1], and soluble vascular cell adhesion molecule‐1 [sVCAM‐1]). Hematological biomarkers were compared between groups using the Kruskal‐Wallis and Wilcoxon Rank‐Sum tests. In multivariable linear regression models, we adjusted for race, number of stroke risk factors, smoking, stroke severity, and antithrombotic use. Transcranial Doppler microemboli presence was compared between groups using chi‐square tests. Results: Levels of all study biomarkers were different between groups. In univariate between‐group comparisons, patients with cancer‐plus‐stroke had higher levels of D‐dimer, sICAM‐1, sVCAM‐1, and thrombomodulin than both control groups; higher levels of thrombin‐antithrombin than patients with cancer‐only; and higher levels of P‐selectin than patients with stroke‐only. Findings were similar in multivariable analyses. Transcranial Doppler microemboli were detected in 32% of patients with cancer‐plus‐stroke, 16% of patients with stroke‐only, and 6% of patients with cancer‐only ( p = 0.005). Interpretation: Patients with cancer‐related stroke have higher markers of coagulation, platelet, and endothelial dysfunction, and more circulating microemboli, than matched controls. ANN NEUROL 2021;90:159–169